Shear Bond Strength of the Metal Bracket to Zirconium Ceramic Restoration Treated by the Nd: YAG Laser and Other Methods: An In Vitro Microscopic Study - Mokhtarpur, Hadi; Nafisifard, Maliheh; Dadgar, Sepideh; Etemadi, Ardavan; Chiniforush, Nasim; Sobouti, Farhad (Journal of Lasers in Medical Sciences, 2020)
Introduction: Providing reliable bonding of the bracket base and the zirconia surface is required to apply orthodontic force. The purpose of this scientific experiment was to evaluate the efficacy of three different methods of surface preparation for Zirconia, including surface roughening, sandblasting and the Nd: YAG laser, in the shear bond strength (SBS) of the orthodontic brackets. Methods: Fifty-four discs of zirconia were divided into three groups of 18: A) Hydrofluoric acid etching, B) sandblasting, and C) Nd: irradiation using the power of 1.5 W for 10 seconds. After bonding the brackets, the samples were slowly thermo-cycled (1000 times) for 24 hours. The SBS test was performed by a universal testing machine at a head speed of 0.5 mm/min. The adhesive remnant index (ARI) was scored at a magnification of 10 in the stereo microscope. All data were collected and analyzed using the variance, Kruskal-Wallis, Tukey, Don, and Weibull tests (α = 0.05). Results: The HF acid etching group (6.11± 0.94 MPa) had the highest SBS, which was followed by the laser group (6 ± 0.61 MPa) and the sandblast group (3.1080 ± 0.82 MPa). There was a significant statistical difference between the laser and HF groups and the sandblast group (P < 0.05) and no significant difference between the HF group and the laser group (P = 0.03). Conclusion: Based on the obtained bond strength, the Nd: YAG laser with a power of 1.5 W could be a substitute treatment method for the HF acid-etching.